Waste Management through the 3R Program in Perspective Sociology of Environmental Communication - Agus Kristian; Tantry Widiyanarti; Aulia Erlinnawati (LPPM Universitas PGRI Sumatera Barat, 2024)
Waste management has become a significant issue in Tangerang Regency, despite the presence of a Final Disposal Site (TPA). The open dumping method at TPA has negative environmental impacts, necessitating government involvement in policy regulation and enforcement. This study aims to analyze government communication strategies in waste management, evaluate the effectiveness of Reduce Reuse Recycle Waste Treatment Sites (TPS 3R), and identify challenges in their implementation. The theoretical framework is based on environmental communication sociology, particularly in managing public participation. This research employs a qualitative method with a case study approach at TPS 3R Mustika over a three-month period. The findings indicate that communication strategies through social media and field activities effectively increase community participation. Furthermore, TPS 3R Mustika is effective as an educational center, despite facing challenges such as low public awareness and limited financial support. In conclusion, increased socialization, cooperation with third parties, and improvements to TPS facilities are necessary. This study offers a reference for other regions in developing sustainable waste management programs. The novelty of this research lies in its strategic communication approach through TPS 3R as an educational center aimed at enhancing public participation in waste management.